The Impact of the Adoption of International Financial Reporting Standards (IFRS) on Information Asymmetry and the Relevance of Financial Statement Values - Evelin Roma Riauli Silalahi; Yan Christin Br. Sembiring; Pani Romauli Elisabet Naibaho (Nomico, 2026)
The adoption of International Financial Reporting Standards (IFRS) has been widely promoted as a mechanism to enhance transparency, comparability, and the overall quality of financial information in capital markets. This study examines the dual impact of IFRS adoption on information asymmetry and the value relevance of financial statements across publicly listed companies in emerging and transition economies. Employing a panel data regression approach combined with the Difference-in-Differences (DiD) method and the Ohlson price model, the study analyzes financial data covering pre- and post-adoption periods. The results demonstrate that IFRS adoption significantly reduces information asymmetry, as evidenced by a marked decline in bid-ask spreads following mandatory adoption. Furthermore, the value relevance of book value per share and earnings per share increased substantially in the post-IFRS period, indicating that financial statements prepared under IFRS provide more decision-useful information to investors. These findings contribute to the growing body of evidence on the economic consequences of global accounting harmonization and offer practical implications for regulators, policymakers, and market participants in countries still deliberating IFRS implementation.